PENGARUH LATIHAN PLYOMETRIC STANDING JUMP OVER TERHADAP TINGGI LONCATAN JUMP SERVICE PEMAIN BOLA VOLI PADA TIM PUTRA PENJASKESREK UNDANA - Arif, Yudabbirul; Louk, Michael Johannes Hadiwijaya; Fufu, Ronald Dwi Adrian; Tajuddin, Al Ihzan (Nusa Cendana University, 2021)
To what extent can the plyometric standing jump over training affect the jump height of the volleyball game jump service on the Men's Penjaskesrek Undana team? This study aims to see the results of the plyometric standing jump over training to increase the jump height of the service jump. This type of research is experimental research. The sample of this research is the men's team volleyball player Penjaskesrek Undana maybe 20 people. Data collection was carried out by means of observation, test and measurement techniques as well as documentation. Based on the results of the study, it can be seen that the significant value that is different between the two groups is 56.4 for the pre-test and 65.3 for the post-test in the experimental group while in the control group, namely 54.7 for the pre-test and 57.2 for the post -test -test. Because the second significant value is greater than 0.05 (significant> 0.05), the data is declared to be normally distributed (accepted). The data table above provides information that by consulting the Fcount and Ftable values, it can be concluded that Ha is accepted and H0 is rejected because Fcount is 6.733 more> Ftable ¬4.413873 and a significant value is 0.007 <0.05 (%) it can be ignored that there is a standing influence. jump against the jump height of men's team volleyball player jump service.